Content Analysis of Higher Order Thinking Skills in Grade V Student Books Elementary School - Aida Rahmi Nasution; Tika Meldina; Atikah Syamsi; Alzairi Hendrik (Al Ibtida: Jurnal Pendidikan Guru MI, 2024)
AbstractLearning outcomes in the learning independence curriculum is that students must have Higher-Order Thinking Skills (HOTS) including for grade V elementary school. So, books must contain HOTS content to support students' HOTS thinking skills. This research aims to analyse the HOTS content in theme 9 student books and describe the amount of HOTS content in theme 9 student books. The research approach used qualitative analysis. The analysis instrument used a checklist sheet according to HOTS indicators. The data analysis technique included 4 stages: data collection; data reduction; data presentation; and conclusion drawing. The results showed HOTS content in theme 9 student books contains HOTS cognitive level 4 (analyzing) containing conceptual and metacognitive knowledge; cognitive level 5 (evaluating) containing conceptual, procedural, and metacognitive knowledge; and cognitive level 6 (creating) containing procedural and metacognitive knowledge. The amount of HOTS content in theme 9 student books are cognitive dimension level C4 (analyzing) by 27.37%, level C5 (evaluating) by 22.11%, and level C6 (creating) by 26.32%. Based on this context, the absorption of all HOTS content in the fifth-grade student book theme 9 amounted to 75.78%.Keywords: higher order thinking skills, student books, elementary school. AbstrakCapaian pembelajaran dalam kurikulum merdeka belajar salah satunya adalah siswa harus memiliki keterampilan berpikir Higher-Order Thinking Skills (HOTS), termasuk untuk kelas V Sekolah Dasar. Maka perlu buku siswa memuat konten HOTS untuk menunjang kemampuan berpikir HOTS siswa. Penelitian ini bertujuan untuk menganalisis konten HOTS pada buku siswa tema 9 dan mendeskripsikan jumlah konten HOTS pada buku siswa tema 9. Pendekatan penelitian menggunakan kualitatif analisis isi (content analysis). Instrumen analisis menggunakan lembar cheklist sesuai indikator HOTS. Teknik analisis data mencakup 4 tahap yaitu pengumpulan data; reduksi data; penyajian data; dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa muatan HOTS pada buku siswa tema 9 terdapat konten HOTS kognitif level 4 (analyzing) memuat pengetahuan konseptual dan metakognitif; kognitif level 5 (evaluating) memuat pengetahuan konseptual, prosedural, dan metakognitif; dan kognitif level 6 (creating) memuat pengetahuan prosedural dan metakognitif. 2) Jumlah konten HOTS pada buku siswa tema 9 terdapat dimensi kognitif level C4 (Menganalisis) sebesar 27.37%, level C5 (Mengevaluasi) sebesar 22.11%, level C6 (mencipta) sebesar 26.32%. Berdasarkan konteks ini keterserapan seluruh konten HOTS pada buku siswa kelas V tema 9 sebesar 75.78%.Kata kunci: keterampilan berpikir tingkat tinggi, buku siswa, sekolah dasar.